Determinan Kebijakan Dividen dengan Pandemi Covid-19 Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Periode 2017-2022 - Qaedi, Razan; Darmansyah; Darminto, Dwi Prastowo (SAFE-Network, 2024)
This research aimed to examine the effect of managerial ownership, institutional ownership, profitability, covid-19 pandemic which moderates of managerial ownership and profitability on the dividend policy with company size as a control variable. The research sample used manufacturing companies which are listed Indonesia Stock Exchange (IDX) in 2017-2022 periods. The sample collection technique has been done by using purposive sampling method with several criteria determined by the researcher. Based on those criteria, it took 55 companies with 330 reseacrh data. The analysis method of this research used panel data regression analysis with the best model is common effect model (CEM) with Eviews version 12 software. The result of the research showed that managerial ownership have no effect on the dividend policy, institutional ownership had effect on the dividend policy, profitability had effect on the dividen policy, covid-19 is unable to modetare the relationship of managerial ownership on the dividend policy and covid-19 is unable to modetare the relationship of profitability (ROE) on the dividend policy.